Influence of different roughness of bed and side walls in an open channel - Siti Natasha, Shamshul Bahri (2014)
Coefficients of roughness, n are characterized as parameters representing the channel roughness and flow resistance. The Manning equation has been recognized as the most proper formulae to represent the open channel flow application. This study is about determining the mean roughness coefficients for an open channel with different bed and side walls roughness. The experiments were conducted at the Hydraulic and Hydrology Laboratory in Universiti Malaysia Pahang. The experiments were performed on a rectangular open channel with glass sides and a flat bed. The size of the rectangular open channel was lOm long, 0.3 m wide and 0.46m deep. The experiments were carried out using two different types of roughness; 5mm gravel and 2 mm gravel. There were two channel conditions, bed and sidewalls having the same roughness, and only the channel bed had the roughness while the sidewalls were smooth. For both conditions; experiments were conducted with certain three fixed slope gradients which are 1:100, 1:300, and 1:500. The fixed flow rates, 4m 31s, 8 m 3/s and 12 m 31 were also set by adjusting the water pump. The data obtained was converted into graph form before performing the analysis. The heights and velocities were recorded at the upper stream and lower stream of the open channel under different roughness conditions. The results showed that the coefficient of roughness for the open channel with wall roughness is higher than the channel without sidewall roughness and larger grain size will give higher roughness coefficient. It also can be concluded that channel slope and surface roughness were the main factors in determining the roughness coefficient.